Healthcare-associated infections in Intensive Care Units: epidemiology and infection control in low-to-middle income countries - Emine Alp; Nizam Damani (2015)
Healthcare-associated infections (HAIs) are major patient safety problems in hospitals, especially in intensive care units (ICUs). Patients in ICUs are prone to HAIs due to reduced host defense mechanisms, low compliance with infection prevention and control (IPC) measures due to lack of education and training, and heavy workload and low staffing levels, leading to cross-transmission of microorganisms from patient to patient. Patients with HAIs have prolonged hospital stays, and have high morbidity and mortality, thus adding economic burden on the healthcare system. For various reasons, in low-to-middle income countries (LMICs), the scale of the problem is huge; each year, many people die from HAIs. In this review, epidemiology of HAIs and infection prevention and control measures in ICUs is discussed, with especial emphasis on LMICs. High rates of HAIs caused by multidrug-resistant organisms (MDROs) are serious problems in ICUs in LMICs. In view of increasing prevalence of MDROs, LMICs should establish effective IPC infrastructure, appoint IPC teams, and provide adequate training and resources. These resources to establish and appoint IPC teams can be released by avoiding ritualistic, wasteful, and unsafe IPC practices, and by diverting resources to implement basic IPC measures, including early detection of infection, isolation of patients, application of appropriate IPC precautions, adherence to hand hygiene, and implementation of HAIs care bundles and basic evidence-based practices.